School Internship Programme An Analytical Review - K., Vijayan; Sharma, Prasun (JOURNAL OF INDIAN EDUCATION, 2019)
Internships, in general, are becoming a widely used programme for students’ experiential learning and it help to fill the gap between the theory learnt and its application in classroom situation. There are different studies conducted in India and abroad about the implementation of school internship programmes as a part of pre-service teacher education programme. The present study is an attempt to review the various studies conducted in this area focusing on the findings and recommendations. Internships have been associated with many benefits for stakeholders, including the student-teachers, schools and other professionals. Internships provide a variety of opportunities for studentteachers to transfer theoretical knowledge to a practical setting.